A novel coronavirus, a novel disease: COVID-19 - Quiroz Carrillo, Carlos Guillermo (2020)
The novel COVID-19 pandemic caused by the SARS-CoV-2 virus is currently challenging humankind. This virus originated in bats has probably been transmitted to humans through pangolins in the Wuhan marine market (China) by the end of 2019. It is spread by droplets of saliva or through contaminated materials, making it extremely important to isolate infected people who may be symptomatic or asymptomatic. The typical clinical features of this disease are fever, dry cough, shortness of breath and general malaise. This member of the coronavirus family shows higher infectivity but lower mortality rates (2–3 %) than its predecessors. Laboratory tests to detect the virus include reverse transcriptasepolymerase chain reaction (RT-PCR) tests or immunoassays.